Relationship Between Capability and Sustainability Performance : Evidence From Indonesia - Iin Rosini; Dani Rahman Hakim (Universitas Muhammadiyah Surakarta, 2020)
A number of studies have proven that capabilities or strategies can influence sustainability performance. This study aims to examine the effect of capability dimensions on sustainability performance within the scope of companies in Indonesia. The population in this study were all accounting and financial managers, control managers, environmental managers, human resources, marketing, operations, and corporate social responsibility (CSR) of 116 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample taken was 185 managers from 45 companies. Data collection methods with questionnaires developed from research (Henri, 2006) and (Staniškis Arbaciauskas, 2009). The data analysis method uses structural equation modeling (SEM) with Smart PLS. The results of this study indicate that sustainability performance is influenced by market orientation and entrepreneurship which are capability dimensions